Gene expression and prognosis of sirtuin family members in ovarian cancer. Issue 24 (12th June 2020) - Zeng, Zhenguo; Huang, Yiming; Li, Yanshu; Huang, Shuying; Wang, Jiao; Tang, Yunliang; Jiang, Yanxia
Abstract : Abstract: Sirtuins (SIRTs), a class of nicotinamide-adenine dinucleotide (NAD)+-dependent deacetylases, involve in modulating carcinogenesis and progression of various malignancies through their regulation of the cancer metabolism. However, the expression profiles and prognostic roles of SIRTs in ovarian cancer (OC) remain unclear. We underscore the transcriptional expression and prognostic significance of SIRTs in OC patients using online databases. Gene Expression Profiling Interactive analysis (GEPIA) was applied to analyze mRNA expression, and Kaplan–Meier plotter was used to evaluate prognostic value. In patients with OC, SIRT1/2/3 were significantly down-regulated, while rest of SIRTs were not significantly changed. High SIRT2/5/6/7 expression was correlated with favorable overall survival (OS), while high SIRT1/4 expression was correlated with poor OS. Additionally, aberrant SIRTs mRNA levels were related to the prognosis of OC patients with different clinicopathological characteristics. This is the first study to integrate bioinformatics approaches intended to identify the expression profiles and prognostic value of SIRTs in OC. These results suggest that SIRTs is related to the prognosis of OC and may be the potential therapeutic interventions in OC.